2021
DOI: 10.21203/rs.3.rs-554799/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nomogram for Predicting Preoperative Regional Lymph Nodes Metastasis in Patients with Metaplastic Breast Cancer: A SEER Population-Based Study

Abstract: Background: Metaplastic breast cancer (MBC) is a rare subtype of breast cancer, and generally associated with poor outcomes. Lymph nodes metastasis (LNM) is confirmed as a critical independent prognostic factor and determine the optimal treatment strategies in MBC patients. We aimed to develop and validate a nomogram to predict the possibility of preoperative regional LNM in MBC patients.Methods: MBC patients diagnosed between 1990 and 2016 in the Surveillance, Epidemiology, and End Results (SEER) database wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…While nomogram can be used to estimate the distantmetastasis risk by integrating the existing clinicopathological factors, improving diagnostic efficiency, reducing time, and economic cost. [21,22] So it is necessary to establish a simple and sensitive prediction model for distant metastasis in MBC patients. The study established a risk prediction model based on the existing evidence to assess the risk of distant metastasis and screen high-risk groups, so as to guide diagnosis and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…While nomogram can be used to estimate the distantmetastasis risk by integrating the existing clinicopathological factors, improving diagnostic efficiency, reducing time, and economic cost. [21,22] So it is necessary to establish a simple and sensitive prediction model for distant metastasis in MBC patients. The study established a risk prediction model based on the existing evidence to assess the risk of distant metastasis and screen high-risk groups, so as to guide diagnosis and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The survival prediction model showed good performance in estimating the prognosis individually. For instance, compared with similar predictive models (30,31), the net benefit of DCA plots in our nomogram was larger, which indicated that the nomogram was a reliable clinical tool for predicting survival.…”
Section: Survival Analysesmentioning
confidence: 80%